Design Analysis Of Remotely Amphibian Vehicle (RAV) – Underwater Drone - Kasno, Mohammad `Afif; Mohd Aras, Mohd Shahrieel; Yeoh, Eik Keong; Abdul Azis, Fadilah; Mohamed Kassim, Anuar; Harun, Mohamad Haniff; Mohd Zambri, Mohd Khairi; Khamis, Alias (Penerbit UTM Press, 2016)
-